Milling-induced transformations in rice flour: implications for bread aging - Zhiqi Wang; Mingshou Lu; Wanshan Yang; Huining Zhang; Lingqi Wei; Xinyu Dong; Jiaxin Zhang; Junru Yu; Menglu Yang; Yue Zhang; Fenglian Chen (Food Chemistry: X, 2025)
This study was aimed to investigate the effects of wet, semi-dry, and dry milling on the quality characteristics of rice flour and the anti-aging quality of rice bread. The wet milled rice flour (WF) exhibited the lowest damaged starch content, at 3.87 %, and had good water absorption and mixing tolerance. During gelatinization process, the gelatinization characteristics of all rice flour decreased. The paste of dry milled rice flour had relatively high G′, G″, and tanδ values, while those of WF were more moderate. Water migration analysis indicated that T22 decreased, T23 decreased first and then increased, A21 rose from 10.99 % to 28.21 %, A22 significantly increased from 36.83 % to 74.82 %, while A23 dropped from 51.43 % to merely 5.14 %. At the 7th day of storage, the WF produced rice bread with a higher sensory score. This study laid a theoretical foundation for the preparation of rice bread.